Pemakaian Kiasan dalam Bahasa Melayu Bengkulu di Kecamatan Teluk Segara Kota Bengkulu - Andra, Vebbi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
The use of figurative language Melayu Teluk Segara Bengkulu in Bengkulu City Bengkulu Malay community in the association spoke in their everyday lives is to use two forms, namely: 1) the proverbial and 2) the parable. While the significance of the use of figurative language Malay Bengkulu can be classified into three, according to the social function of the usefulness of the figurative, are: 1) satire on actions (behavior) that a person or group of people, 2) counsel (teaching guides) so that someone or a group of people can live their lives well, and 3) the credit for an achievement of a person or group of people.